ANALISIS YURIDIS TERHADAPSTATUS HAK KEPEMILIKAN PERMUKIMAN PENDUDUK DI ATAS AIR - Irman, Irman; Adhayanto, Oksep; Sari, Rany Kartika; Suryadi, Suryadi (UI Scholars Hub, 2021)
This research was conducted to examine whether Settlement on the water can be given ownership status as the right to land in theUUPA. The purpose of this study is to find out and analyze settlements on water, can the status of land rights be given as stipulated in the legislation, and with the hope that people who have houses and settlements on the water can obtain proof of ownership of land and buildings on the water. The research method usedis normative research, with a statutory approach and a historical approach. The results showed that although the Regulation of the Minister of Agrarian and Spatial Planning /Head of the National Land Agency of the Republic of Indonesia Number 17 of 2016 concerning Land Arrangement in Coastal Areas and Small Islands provides an opportunity to be given the right to land against settlements on the water in legal concept This is contrary to the UUPA which only regulates the types of land rights that are only granted to land and buildings that stand on land.